PENDIDIKAN LINGKUNGAN HIDUP DALAM KONSEP ISLAM - Dety Mulyanti (Nizham Jurnal Studi Keislaman, 2016)
Education for human life is an absolute necessity, which must be met for life. Without education it is impossible a group of people can thrive in line with aspirations for advanced, prosperous, happy according to the concept of their worldview. To advance their lives that then become the main means of education that needs to be managed systematically and consistently. Therefore in this paper will be presented on Islamic education, good sense and function, then about tri education center. Education is the main factor in the human person formation. Education plays an important role in shaping the human person is good or bad according to the size of the normative. On the other hand the process of development and human education does not just happen and influenced by the process of education in the formal education system (schools) only. Mankind for life will always get the influence by family, school and community. In other words, the process of development of human education is to achieve maximum results depends not only on how the education system happen. But it also depends on the educational environment besides the formal environment. Islamic religion is concerned about the environment into the early formation of human character to the extent that there are words of The Prophet stated that for better or worse depending on the merits of the surrounding environment. Islamic education as a liberating people from the threat of apostasy bring men to “Neraka”. Create the human becomes a servant of God who have a happy life harmony and balance in the world and the Hereafter.